Kontribusi Explosive Power Otot Tungkai Dan Kecepatan Lari Terhadap Hasil Lompat Jauh Gaya Jongkok Siswa Kelas VII SMP Muhammadiah I Pekanbaru - Yadikha, Fadilla Putri; ., Zulrafli (CV. ITTC INDONESIA, 2024)
The aim of this research was to determine the contribution of leg muscle explosive power and running speed to the long jump results of squatting style for class VII students at SMP Muhammadiah 1 Pekanbaru. This type of research is correlational research. The population in this study was class VII students at SMP Muhammadiah 1 Pekanbaru, totaling 31 male and female students. The sample used in this research was only male students, totaling 18 students. The instruments used were the standing broad jump test, 30 meter sprint and long jump test. The conclusions of this research are: 1) There is a contribution of leg muscle explosive power to the squat style long jump results of Class VII Students of Muhammadiah I Middle School Pekanbaru. The calculated r value = 0.656. The coefficient of determination = 43.0%. 2) There is a contribution of running speed to the long jump results of the squat style of Class VII Students of SMP Muhammadiah I Pekanbaru. The calculated r value = 0.503. The coefficient of determination = 25.3%. 3) There is a contribution of leg muscle explosive power and running speed to the squat style long jump results of Class VII Students of Muhammadiah I Middle School Pekanbaru. The calculated r value = 0.698. The coefficient of determination = 48.7%.